Immunohistochemical analysis of pancreatic islets of platypus (Ornithorhynchus anatinus) and echidna (Tachyglossus aculeatus ssp.). Issue 4 (9th February 2015) - He, Chuan; Myers, Mark A.; Forbes, Briony E.; Grützner, Frank
Abstract Monotremes have undergone remarkable changes to their digestive and metabolic control system; however, the monotreme pancreas remains poorly characterized. Previous work in echidna demonstrated the presence of pancreatic islets, but no information is available for platypus and the fine structure has not been described for either monotreme. Based on our recent finding that monotremes lack the ghrelin gene, which is expressed in mouse and human pancreatic islets, we investigated the structure of monotreme islets in more detail. Generally, as in birds, the islets of monotremes were smaller but greater in number compared with mouse. β‐cells were the most abundant endocrine cell population in platypus islets and were located peripherally, while α‐cells were observed both in the interior and periphery of the islets. δ‐cells and pancreatic polypeptide (PP)‐cells were mainly found in the islet periphery. Distinct PP‐rich (PP‐lobe) and PP‐poor areas (non‐PP‐lobe) are present in therian mammals, and we identified these areas in echidna but not platypus pancreas. Interestingly, in some of the echidna islets, α‐ and β‐cells tended to form two poles within the islets, which to our knowledge is the first time this has been observed in any species. Overall, monotreme pancreata share the feature of consisting of distinct PP‐poor and PP‐rich islets with other mammals. A higher number of islets and α‐ or β‐cell only islets are shared between monotremes and birds. The islets of monotremes were larger than those of birds but smaller compared with therian mammals. This may indicate a trend of having fewer larger islets comprising several endocrine cell types during mammalian evolution.